TYPOLOGY ANALYSIS AND RELATIONSHIP BETWEEN STUNTING PREVALENCE, ECONOMIC GROWTH AND GRDP PER CAPITA IN PROVINCE OF BALI - Yudha, I Made Endra Kartika; Pratiwi, Ida Ayu Meisthya; Saskara, Ida Ayu Gde Dyastari; Anandari, I Gusti Agung Ayu Apsari (Universitas Mataram, 2024)
This study aims to determine the dynamics of the growth pattern and structure of each city/regency in the Province of Bali and try to see its relationship with the stunting prevalence in the Province of Bali. The analytical method used in this research is the Klassen Typology analysis technique and the Spearman Rank Correlation. The results of the Klassen Typology analysis, when correlated with stunting data, show that the Buleleng area which is a developed area (quadrant 1) has a high stunting prevalence of 10.30%, while Tabanan is a relatively underdeveloped area (quadrant 4) has a stunting prevalence below the average Province of Bali (6.6%). The results of the correlation test with the Spearman Test showed that there was no significant relationship between economic growth and GDP per capita partially on the stunting prevalence in Province of Bali, but each of the two variables had a negative relationship. Thus, further research is needed regarding other facts regarding the stunting prevalence in the Province of Bali, so that it can provide a clear picture of the variables that influence the stunting prevalence in each district/city.